Dysgerminoma in Pseudohermaphroditism: A Case Report - Pun, Rashmey; Pudasaini, Sujata; Mahaseth, Rita; Shrestha, Kriti (Nepalese Medical Journal, 2020)
Female pseudohermaphroditism occurs when normal ovaries are present but the body is partially masculinized as individuals with congenital adrenal hyperplasia, also known as adrenogenital syndrome. This is an inherited disorder that accounts for about one-half of all cases of human intersexuality. We report a case of a 24-year-old male presenting with abdominal pain and increasing abdominal distension for one month. Computed tomography scan revealed large multiloculated heterogeneously enhancing solid –cystic lesion in the abdominopelvic cavity– malignant gonadal mass, gross ascites, and visualization of the poorly formed elongated uterus-like structure in the recto-uterine pouch and phallus-like structure with non-visualization of bilateral testes. Histopathology report suggested germ cell tumor and immunohistochemistry confirmed the diagnosis of dysgerminoma. Since dysgerminoma is sensitive to platinum-based chemotherapy patient was subjected to chemotherapy and the patient showed a good response. The patient underwent exploratory laparotomy with right salpingo-oophorectomy with omentectomy and appendectomy.